The activities of Gajret in the smaller settlements and towns of Bosnia and Herzegovina during the interwar years – the cases of Lukavac and Puračić - Hamzić, Omer (Historical Thought, 2025)
In an attempt to find an answer to the question of the realimportance of Gajret in the sociallife of the Muslims living in smaller settlements and towns of Bosnia and Herzegovina during the interwar years, the author provides a detailed insight into the activities of Gajret in the vicinity of Tuzla, specifically in Lukavac and Puračić, smaller neighboring settlements which are different when it comes to their socio-economic development, and partially in the social structure of the populatio nitself. The central questions of this thematic are organizational and staff problems and the connections of the Gajret local boards and committees with local politics, along with the important cultural and educational activities of this association. This article can therefore be used as an illustration for the activity of Gajret in the smaller settlements of Bosnia and Herzegovina, respectively, their activities in the field. This article is based on the original archival documents, to a lesser extent complemented by fragmentary notes, oral testimonies and memories.